Tubal flushing with oil-based contrast during hysterosalpingography versus tubal flushing by hysterosalpingo-foam sonography in infertile women undergoing fertility work-up: study protocol of a randomised controlled trial (FOil study) - Madelon van Wely; Harold R Verhoeve; Judith E Bosmans; Johannes R Anema; Jan Peter de Bruin; Jaap Stoker; Ben Willem J Mol; Danah Kamphuis; Janette P M Huijser; Nienke van Welie; Esther Kuijper; Angelique J C M van Dongen; et al. (BMJ Open)
Introduction Hysterosalpingography (HSG) and hysterosalpingo-foam sonography (HyFoSy) are commonly used tubal patency tests during the fertility work-up. Besides its diagnostic purpose, HSG with oil-based contrast can also be applied for its fertility-enhancing effect, by tubal flushing. HyFoSy is considered as less painful compared with HSG, it lacks exposure to iodinated contrast medium and ionising radiation. The fertility-enhancing effects of HyFoSy are less studied and randomised controlled trials comparing pregnancy rates after HSG and HyFoSy are lacking. This study (FOil study) is initiated to compare the effectiveness of tubal flushing during HSG with oil-based contrast and HyFoSy.Methods and analysis The FOil study is a nationwide, multicentre, open label, randomised controlled trial with a superiority design. Infertile women with an indication for tubal patency testing during their fertility work-up will be randomly assigned to HSG with oil-based contrast medium or HyFoSy. The primary outcome is conception within 6 months after randomisation leading to live birth. To demonstrate or refute an 8% difference in conception leading to live birth in favour of HSG with oil-based contrast, 1102 women will be included in the trial. A cost-effectiveness analysis from a societal perspective will be performed alongside the trial.Ethics and dissemination The trial is approved by the Medical Ethics Review Committee of the Amsterdam University Medical Centers (Ref. No. 2022.0884, date: 17 March 2023) and by the boards of the participating hospitals. The findings will be disseminated in peer-reviewed journals and participants will be informed through the patient organisation.Trial registration number NCT05882188.